2020
DOI: 10.1111/arcm.12633
|View full text |Cite
|
Sign up to set email alerts
|

Archaeometric Provenance Constraints for Early Medieval Sparse Glazed Pottery from Donoratico (Livorno, Italy)

Abstract: suggested the application of a lead oxide flux to an unfired non-calcareous ceramic body, in accordance with late Antique and early-Medieval traditions. The isotopic investigation of the glazes also suggested different sources for PbO, which was frequently applied as a mix of different metal batches. The Pb isotopic record identified the Southern Tuscany districts (Campiglia Marittima and Colline Metallifere) and a source controlled by the Carolingian kings in the northern districts of Central Europe (either i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous studies on sparse-glazed ware manufacture in Donoratico confirmed the existence of dedicated ateliers in the area and the exploitation of local raw materials [59].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Previous studies on sparse-glazed ware manufacture in Donoratico confirmed the existence of dedicated ateliers in the area and the exploitation of local raw materials [59].…”
Section: Discussionmentioning
confidence: 67%
“…Previous archaeological studies on early medieval ceramic production in Tuscany have stressed the existence of a fragmented manufacturing base that consisted of only a few dispersed production sites until the 10th century. Within this framework, the archaeological evidence suggested that there was a local manufacture of cooking, table and storage wares, with a scattering of highly skilled ateliers being documented in some areas, including the Colline Metallifere [56][57][58][59].…”
Section: Archaeological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The lead present in archaeomaterials can be characterised by lead isotope analysis (LIA), a technique that has been used since the 1960s (Grögler et al, 1966;Brill and Wampler, 1967;Gale and Stos-Gale, 2000). Studies using LIA on glazes have generally focused on technological choices and specific distribution networks, as well as on lead sources (Mason et al, 1992;Wolf et al, 2003;Stos-Gale, 2004;Iñañez et al, 2010;Walton and Tite, 2010;Shen et al, 2019;Fornacelli et al, 2020;Medeghini et al, 2020;Chang et al, 2021).…”
Section: Highlightsmentioning
confidence: 99%
“…Provenance studies help unravel the mysteries of human history, trade, and cultural exchange. This type of research has been developed on a number of materials (see [2] and references therein), including pottery (and their corresponding clays) [3,4], stones [5][6][7], metals (e.g., [8,9]), mortars/plasters (e.g., [10,11]), glasses [12], glazes (e.g., [13,14]) and pigments (e.g., [15,16]). The strategy to trace the source of the corresponding raw materials is specific to every type of material.…”
Section: Introductionmentioning
confidence: 99%